COMBINING ABILITY ANALYSIS FOR YIELD AND QUALITY TRAITS IN MAIZE ( TRAITS IN MAIZE (Zea mays Zea mays L.) HYBRIDS L.) HYBRIDS - NARAYAN RAM GURJAR; AMIT DADHEECH; SANJAY KUMAR (The Bioscan, 2019)
Thirty-nine hybrids of maize were developed by crossing 13 lines with 3 testers. These hybrids along with parents and 3 standard checks were evaluated during kharif-2017 for 14 characters. The mean sum of squares of hybrids, lines and testers, were significant for majority of traits. Among inbred lines, EI-2840 had significant GCA effects for grain yield per plant (27.19) and yield component traits like number of grain rows per ear (1.92), harvest index (2.63), maturity traits like, days to 50 per cent tasseling (1.39), days to 50 per cent silking (1.19) and quality traits like oil content (0.34), protein content (0.87) and starch content (2.97), indicated that best general combiner for these traits, while in male parent, EI-1110-2 was the best general combiner for yield contributing traits viz., grain yield per plant (4.76), harvest index (1.11), number of grain rows per ear (0.81), and quality traits viz., oil content (0.08), protein content (0.21). Hybrid EI-3823 x EI-1110-2 (37.21) followed by hybrid EI-2817 x EI-1175-2 (34.26), EI-2543x EI-1175-2 (33.76) expressed positive significant SCA effects for yield and contributing traits. Hence these hybrids embark to be high promising combination for virtual exploitation.